Analysis of Artificial Intelligence (AI) Recommendation Systems to Support Itsuki Matcha as a Micro, Small, and Medium Enterprise (MSME) in Indonesian Social E-Commerce - Esau Gultom; Dika Jatnika (UNIVED Press, 2026)
This study examines the implementation of artificial intelligence–based recommendation systems through Meta Ads and Odoo ERP in the micro, small, and medium enterprise (MSME) Itsuki Matcha. The research aims to evaluate how AI-driven digital advertising and operational systems contribute to brand awareness, customer interest, and sales performance. A mixed analytical approach was employed, combining the EPIC Model to assess advertising effectiveness with experimental budget variations in Meta Ads and operational evaluation of Odoo ERP. The findings indicate that communication-focused advertising content performs most effectively in attracting audience attention and conveying product information. While the Meta Ads recommendation system initially faced a cold-start condition, performance improved as the algorithm entered a learning phase, leading to higher engagement and the first recorded sales conversions. In addition, Odoo ERP enhanced operational efficiency by automating inventory management and synchronizing sales data, despite limitations in activating its AI recommendation features due to insufficient historical data. Overall, the study demonstrates that AI-based systems can support early-stage MSME growth by strengthening digital visibility and operational accuracy, although sustained implementation and longer observation periods are required to achieve stable financial performance and scalability.